2002
DOI: 10.5741/gems.38.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Yellow Cultured Pearls from The Black-Lipped Oyster <i>Pinctada Margaritifera</i>

Abstract: colored strands marketed today may include a mix of cultured pearls from the P. maxima and P. margaritifera (Federman, 1998b) or consist only of cultured pearls that originate from the P. margaritifera. The latter may include several in the following yellow hue range: yellow, greenish yellow, brownish yellow, or grayish yellow. This makes some of them difficult to distinguish from similar-color cultured pearls from the P. maxima.Identification of the mollusk species in which a pearl was cultured is becoming a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
7

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 8 publications
3
20
0
7
Order By: Relevance
“…The ITS2 sequence of PMX4 differed from P. margaritifera by only two single nucleotide polymorphisms (Table 1). Based on our overall results, we believe that the visual assignment of species origin was incorrect, as it is well known that P. margaritifera not only produces grey to black pearls, but also yellowish to white ones, which are very similar in color to pearls from P. maxima [10], [19]. A recent study [45] found a Japanese P. maxima oyster, identified based on its morphology clustering with P. margaritifera , on the basis of its cox1 sequence and concluded that the mismatch was due to inaccuracy of the morphological measurement.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The ITS2 sequence of PMX4 differed from P. margaritifera by only two single nucleotide polymorphisms (Table 1). Based on our overall results, we believe that the visual assignment of species origin was incorrect, as it is well known that P. margaritifera not only produces grey to black pearls, but also yellowish to white ones, which are very similar in color to pearls from P. maxima [10], [19]. A recent study [45] found a Japanese P. maxima oyster, identified based on its morphology clustering with P. margaritifera , on the basis of its cox1 sequence and concluded that the mismatch was due to inaccuracy of the morphological measurement.…”
Section: Resultsmentioning
confidence: 79%
“…Thus there is significant interest in being able to scientifically document the provenance of both historic natural pearls [8], [9] and modern cultured pearls. This is rarely possible for the most valuable white to slightly cream-colored pearls using current methods such as UV-visible photospectrometry and micro-Raman spectroscopy [10], [11], [12], [13]. The higher value of natural pearls has led to many fraudulent attempts to pass off cultured pearls as natural ones [14], [15], [16].…”
Section: Introductionmentioning
confidence: 99%
“…Tahitian Cultured Pearls. The red long-wave fluorescence shown by the Mexican cultured pearls is not seen in Tahitian cultured pearls, which are typically inert to slightly reddish brown (Elen, 2002;figure 9). Porphyrins are among the most highly fluorescent compounds in nature (Guilbault, 1990), and according to Hurwit (1992;2000), red fluorescence is a characteristic feature of pearls from the Gulf of California.…”
Section: Discussionmentioning
confidence: 99%
“…As there is commonly a large price gap between natural pearls and cultured pearls, the trade relies on specialized gemmological laboratories to identify pearls and to distinguish natural from cultured pearls. Identification if a pearl grew as natural or cultured pearl is commonly based on radiography, X-ray luminescence, and X-ray computed µ-tomography, combined with X-ray fluorescence (EDXRF), Raman microspectrometry, UV-Vis-NIR reflectometry and meticulous microscopic examinations (Anderson 1931;Elen 2002;Hänni 2006;Barnard and de Waal 2006;Sturman 2009;Krzemnicki et al 2010). Recently, radiocarbon dating appeared as a new approach in pearl testing (Hänni 2008;Krzemnicki 2010;Hainschwang et al 2010).…”
Section: Introductionmentioning
confidence: 99%